A Retrospective Cohort Study of Treatment Outcome among HIV positive and HIV negative TB patients in Chandigarh, India - Saini, Shveta; Singh, Mukhmohit; Garg, Anil (Indian Journal of Community Health, 2016)
Background: Tuberculosis (TB) and the HIV epidemics have been well known previously but now these are emerging as a combined epidemic to pose new public health challenges. TB is the most common opportunistic infection found among HIV positive individuals. Aims & Objective: To find the prevalence of HIV infection among the TB patients diagnosed and put on treatment under RNTCP. 2. To assess their treatment outcomes in Chandigarh. Material & Methods: The present study was designed as a retrospective cohort study among the adult population (>18 years) in Chandigarh from April 2012 - March 2014. All the TB patients registered for treatment at the 17 DMCs of Chandigarh, during this period were taken as the study population. The treatment outcome among TB-HIV co-infected patients was compared with those having only Tuberculosis. Results: From 1st April 2012 - 31st March 2013, a total of 3,551 patients were registered under RNTCP for treatment of tuberculosis. Among the total patients put on DOTS (3,551), 63.2% (2,246) were males and 36.7% (1,305) were females. A total of 3,516 TB patients had their blood tested for HIV. Out of these patients, 88 (2.47%) were tested positive for HIV. HIV positive status was also found to be significantly associated with occurrence of extra pulmonary tuberculosis (X2= 17.42; df 2; p 0.0001). Category – II treatment was found to be slightly more among the HIV positive TB patients as compared to the HIV negative patients. From the total sample, 2.19% (78) patients were later diagnosed as having drug resistant tuberculosis with only one (01) patient being co-infected with HIV. Out of all the TB-HIV co-infected patients, 29.55% were declared cured at the end of the treatment. A total of 63.64% of co-infected patients had completed their treatment. Death as an outcome was significantly associated with HIV positive status (1.14%) as compared to HIV negative patients. Conclusion: Integration of TB-HIV collaborative activities at every level will strengthen our battle to control TB and HIV globally.